Prospective physics teacher’s ability in developing HOTS questions: CRI analysis - Nurul Ain (Momentum: Physics Education Journal, 2021)
Higher order thinking skills (HOTS) are very important skills to be taught to students in the 21st century. The role of teachers is very important in improving students' high-level skills. This study aims to determine whether or not prospective physics teachers have misconceptions in compiling HOTS cognitive questions. The emergence of miscon-ceptions shows that the ability of prospective physics teachers is still low in composing HOTS cognitive questions. The research subjects were all final semester prospective physics teachers who took the learning evaluation course at the Universitas PGRI Kanjuruhan Malang in the even semester of 2019/2020. The data collection technique is documentation. The data is taken from the final project document in the learning evaluation course, where prospective physics teachers are asked to make cognitive ques-tions from levels C1 to C6 and are asked to state their beliefs about the questions they have made. The data were analyzed in the descriptive qualitative way to determine the misconceptions of prospective physics teachers. The results showed that prospective physics teachers were not yet able to compile HOTS cognitive questions. Recommenda-tions for the preparation of HOTS questions are also given in this paper.